Phytoremediation of arsenic-contaminated water: the role of antioxidant metabolism of Azolla caroliniana Willd. (Salviniales) - Leão,Gabriela Alves (2017)
ABSTRACT Phytoremediation has proven to be an efficient technology for removing arsenic (As) from water, but the plants used in this process need to be tolerant to the damage caused by As. The toxic effect of As on growth and functioning of the antioxidant system was studied in individual plants of Azolla caroliniana exposed to five concentrations of As (0.0, 0.25, 0.5, 1.0 and 1.5 mg L-1) for the course of five days. Growth, As absorption, enzymatic activity, total and non-protein thiols and anthocyanin content were assessed. Azolla caroliniana was able to take up large amounts of the pollutant, reaching As concentrations of 386.1 µg g-1 dry weight without saturating the absorption mechanism. The tolerance index and the growth of A. caroliniana decreased with the increased As uptake. Superoxide dismutase, peroxidases, catalases and glutathione reductase activities increased at lower doses of As and subsequently declined with higher concentrations, whereas ascorbate peroxidase activity was reduced in all treatments. Unlike the enzymatic defence system, anthocyanin and thiol content increased consistently in all treatments and showed a positive correlation with As concentration. Therefore, the increased synthesis of non-enzymatic antioxidants is most likely the main factor responsible for the high As tolerance of A. caroliniana.